Reconsideration of the genera Merogomphus Martin, 1904, and Anisogomphus Selys, 1857, including erection of a new genus, with a new species and discussion of additional specimens from Cambodia - Kosterin, Oleg E. (Zootaxa, 2016)
In the current sense, Merogomphus Martin, 1904, is an artificial genus. It includes two unrelated groups of species: those with lyrate cerci with or without an outer spine and those with simple cerci, plus two species with large and broad epiproct branches placed in Merogomphus obviously in error. At the same time a number of species similar and obviously related to the former group were described from China in the genus Anisogomphus Selys, 1857. To resolve this taxonomic tangle, the genus Merogomphus is restricted to include only species with lyrate cerci: M pavici (Martin, 1904) (the type species), M. longistigmus (Fraser, 1922), M. vandykei (Needham, 1930), M. femoralis (Laidlaw, 1931), M. vespertinus (Chao, 1999) and M. torpens (Needham, 1930). A new genus Euthygomphus (type species: Leptogomphus martini Fraser, 1922) is erected to contain species with simple cerci and moderately divergent epiproct branches, formerly attributed to either Merogomphus or Anisogomphus: Euthygomphus parvus (Krüger, 1899) comb. nov., E. martini (Fraser, 1922) comb. nov., E. koxingai Chao, 1954 comb. nov., E. chaoi Liu 1991 comb. nov., E. jinggangshanus Liu, 1991 comb. nov., E. yunnanensis Zhou et Wu, 1992 comb. nov. Euthygomphus schorri Kosterin, 2016, sp. nov. is described (type locality: Cambodia, Mondulkiri Province, 3.5–3.8 km ESE of Sen Monorom, holotype in RMNH), A new synonymy Merogomphus chaoi Yang & Davies, 1993 = Anisogomphus pinratani Hämäläinen, 1991, and a new combination Anisogomphus tamdaoensis (Karube, 2001) comb. nov. are proposed. The published records of ‘Merogomphus parvus’ from Laos, Thailand, Vietnam, Cambodia and Vietnam are reidentified as E. yunnanensis, and new records and illustrations of this species from Cambodia are provided.